Kajian Kesiapan Sekolah Menengah Pertama Di Kabupaten Manokwari, Provinsi Papua Barat Dalam Melaksanakan Kurikulum Tingkat Satuan Pendidikan (KTSP) 2006 - Sri Hartini, ; Alexander Yaku, ; Frenki Arthur Paiki, ; Purwaningsih, (Pendidikan Sekolah Dasar, 2010)
The purpose of this research is to study the readiness of Junior High School at Manokwari district, Papua Barat Province on applying the unit of education degree curriculum.  The study was focused on the readiness of the school on applying all the curriculum components in teaching and learning process, and the availability of the curriculum supporting component. The results of this study showed that the Junior High Schools at Manokwari district has ready to apply the curriculum. The range of criteria, as an indicator, was between Agree to Very Agree. In contrast, the supporting component in applying the curriculum was far from sufficient. The range of criteria on this component was 83.3% Disagree.